Dynamic contrast-enhanced ultrasound and elastography assess deltoid muscle integrity after reverse shoulder arthroplasty - Fischer, Christian; Krammer, Daniel; Hug, Andreas; Weber, Marc-André; Kauczor, Hans-Ulrich; Krix, Martin; Bruckner, Thomas; Kunz, Pierre; Schmidmaier, Gerhard; Zeifang, Felix (Journal of shoulder and elbow surgery, 2017)
Background: The outcome after reverse shoulder arthroplasty (RSA) depends on the condition of the deltoid muscle, which we assessed with new ultrasound modalities and electromyography (EMG). Contrast-enhanced ultrasound (CEUS) and acoustic radiation force impulse (ARFI) were applied to assess perfusion and elasticity of the deltoid muscle compared with the clinical and functional outcome. Methods: The study recruited 64 patients (mean age, 72.9 years) treated with RSA between 2004 and 2013. The deltoid muscle was examined with EMG and ultrasound imaging. Functional scores such as Constant score and American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form score were assessed. Among other CEUS parameters, the wash-in perfusion index, time to peak, and rise time were compared between the operated-on and contralateral shoulders as well as between patients with above-average and below-average outcome. The stiffness of the deltoid muscle was analyzed with ARFI. Results: After RSA, deltoid perfusion (wash-in perfusion index, Δ = −12% ± 22%, P = .0001) and shoulder function (Constant score, Δ = −14 ± 24, P < .0001) were both inferior compared with the contralateral side. This perfusion deficit was associated with a limited range of motion (time to peak and anteversion: r = −0.290, P = .022). Deltoid perfusion was higher in patients with above-average outcome (rise time, Δ = 33% ± 13%, P = .038). The operated-on deltoid muscles showed higher stiffness than the contralateral muscles (ARFI, Δ = 0.2 ± 0.9 m/s, P = .0545). EMG excluded functionally relevant axillary nerve injuries in the study population. Conclusions: CEUS revealed reduced mean perfusion of the deltoid muscle after RSA. Reduced perfusion was associated with limited range of motion and below-average outcome. Functional shoulder impairment after RSA might be predicted by noninvasive CEUS as a surrogate parameter for the integrity of the deltoid muscle.
Available online 30 June 2016
Gesehen am 22.08.2019